Estudo da influência alimentar na etiologia da urolitíase em cordeiros - Branchini, Naiana da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The sheep industry is a growing activity in the Brazilian livestock and plan is developed in different ways (extensive, semi-intensive, intensive). In creations, the incidence of urolithiasis has been observed. Due to this fact, the study of aspects related to the genesis, prevention, diagnosis and treatment becomes necessary and current. Incorporated to the onset of urolithiasis, power is one of the most important predisposing factors in stone formation, particularly in feedlot animals fed diets with higher volume of concentrates and little fiber. This project aims to evaluate the influence of power in the constitution of urolithiasis in sheep. Specifically, two types of diets, which differed ratio calcium/phosphorus (Ca/P) were tested. The effect of feeding on the animals was assessed by laboratory tests (serum urea and creatinine, urinalysis, concentration of phosphorus, magnesium and calcium in the blood and urine) and confirmation of diagnosis by clinical signs. 30 male sheep were used, weighing between 18 and 20kg and 4 months of age were randomly divided into 2 groups according to diet: Group 1 (n=15) - phosphorus level of 0.43% and Group 2 (n=15) - phosphorus level of 0.65%. The animals were fed the diets for 90 consecutive days and water ad libitum. Moment (M) of crop material M0 - immediately before the beginning of treatment and at 15 days intervals at M1, M2, M3, M4, M5, M6. Blood and urine samples for urinalysis, serum urea and creatinine and phosphorus concentration, Magnesium and Calcium were harvested. Animals with clinical signs urolithiasis were evaluated by physical examination, when confirmed the diagnosis, undergoing medical treatment (retrograde urethral hydropropulsion) and, when necessary, urethrostomy

A ovinocultura é uma atividade em crescimento no plano pecuário brasileiro e é desenvolvida de maneiras diversas (extensiva, semi intensiva, intensiva). Nas criações, tem sido observada a incidência de urolitíase. Devido a este fato, o estudo de aspectos relacionados à gênese, prevenção, diagnóstico e tratamento torna-se necessário e atual. Incorporada ao aparecimento da urolitíase, a alimentação é um dos fatores predisponentes mais importantes na formação dos cálculos, principalmente em animais em confinamento recebendo dietas com maior volume de concentrados e pouca fibra. Este projeto tem como objetivo avaliar a influência da alimentação na constituição da urolitíase em ovinos. De modo específico, foram testadas dois tipos de dietas, as quais diferenciaram-se proporção cálcio/fósforo (Ca/P). O efeito da alimentação sobre os animais foi avaliado através de exames laboratoriais (ureia e creatinina séricas, urinálise, concentração de fósforo, magnésio e cálcio no sangue e na urina) e confirmação do diagnóstico por sinais clínicos. Foram utilizados 30 ovinos machos, com peso entre 18 e 20Kg e 4 meses de idade, divididos aleatoriamente em 2 grupos de acordo com a dieta: Grupo 1 (n = 15) - nível de fósforo de 0,43% e Grupo 2 (n = 15) - nível de fósforo de 0,65%. Os animais receberam as dietas por 90 dias consecutivos e água ad libitum. Momentos (M) de colheita de material: M0 - imediatamente antes do início da dieta e em intervalos de 15 dias nos momentos M1, M2, M3, M4, M5, M6. Foram colhidas amostras de urina e sangue para urinálise, dosagem sérica de ureia e creatinina e concentração de fósforo, Magnésio e Cálcio. Os animais com sinais clínicos urolitíase foram avaliados pelo exame físico, quando confirmado o diagnóstico, submetidos a tratamento clínico (hidropropulsão retrógrada uretral) e, quando necessária, uretrostomia
Keywords: Ovino - Criação; Rins - Doenças - Diagnóstico; Aparelho urinario - Calculos; Calculos (Patologia); Nutrição animal; Animal nutrition; Sheep